Characterizing Patients and Treatment Patterns in Moderate-to-severe Atopic Dermatitis in Finland: A Population-based Study Using National Health Data - Remitz, Anita; Peltonen, Essi J.; Korhonen, Laura; Nortamo, Pekka; Iso-Mustajärvi, Ilona; Prami, Tuire; Oinonen, Lasse; Gittens, Beatrice; Von Arx, Lill-Brith; Porsdal, Vibeke (Acta dermato-venereologica, 2025)
This observational study evaluated demographics, disease characteristics, and treatment patterns in children, adolescents, and adults with moderate-to-severe atopic dermatitis (AD) and compared comorbidities (adults only) and healthcare resource use with those of matched reference subjects without moderate-to-severe AD in Finland between 2016 and 2020. A total of 68,216 patients with moderate-to-severe AD and a reference population of 338,325 people without moderate-to-severe AD were identified and included in the study. Among children aged 0–11 years in the moderate-to-severe AD cohort, most were diagnosed with AD and were identified to have moderate-to-severe AD before they reached 4 years of age (92.4% and 79.3%, respectively). Atopic disorders and psychiatric, gastrointestinal, and other diseases were more common in adults with moderate-to-severe AD than in the reference population. Regardless of age, patients with moderate-to-severe AD had a higher number of primary and secondary healthcare visits annually compared with the reference population. Across all 3 age groups, topical corticosteroids and emollients were the 2 categories of AD medications most frequently used throughout the study period. In adults, the use of methotrexate and dupilumab increased over the course of the study. Moderate-to-severe AD affects people of all ages in Finland.